KORELASI KETERAMPILAN MENYIMAK TEKS BERITA DENGAN KETERAMPILAN MENULIS TEKS BERITA - Putri, Wahyuni; Ratna, Ellya (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT The purpose of this research there are three. First, describing news text writing skills. Second, describe the skills of listening to news texts. Third, describe the correlation of listening to news text skills with news text writing skills. This type of research is quantitative with descriptive method. The design of this research is correlational. The population in this research were all eighth grade students of class VIII SMP Negeri 34 of Padang who were enrolled in the 2018/2019 school year, namely 223 student. There are two variable in this research, namely the dependent variable (Y) the ability to write news text and the independent variable (X) the skill of listening to news text. The data in this study were scores on the skills of writing news texts and skills score listening to news texts. The instrument used is a test, which is an objective test for listening to news text skills and performance tests for news text writing skills. The results of this research are three. First, news text writing skills of class VIII SMP Negeri 34 of Padang are in good qualification (80,75). Second, listening to the news text skills of clas VIII SMP Negeri 34 of Padang are in good qualification (77,57). Third, listening to news text skill correlates with news text writing skills. Based on this , it can be conclude that to improve writing skills, listening skills must be improved. Kata kunci : Korelasi, Menyimak, Menulis, dan Teks Berita